The prevalence of os acromiale - Yammine, Kaissar (2013)
Os acromiale (OA) results from a failure of consolidation between the ossification centers of the acromial epiphysis. Its prevalence and its interactions with ancestry, gender, laterality, and side have been variously reported in the literature. The aims of this review are to provide an accurate estimate of OA prevalence and to investigate its association with other variables in an attempt to comprehend its etiology. Twenty‐three studies met the inclusion criteria. The results of meta‐analyses of large‐sample studies revealed: (a) a crude overall prevalence of 7.0%, (b) a crude cadaveric prevalence of 7.6%, (c) a crude archeological (skeletal) prevalence of 5.6%, (d) a crude radiological prevalence of 4.2%, (e) a true anatomical prevalence of 9.6%, (f) a significantly higher frequency in persons of black ancestry than in persons of white, Native American and Middle Eastern ancestries (OR ≈ 3), (g) significantly higher unilateral and bilateral frequencies in black ancestry (OR of 2 and 4, respectively), (h) nonsignificant interactions of OA frequency with gender and side. The commonest type of OA was the meso‐acromion type (76.6%). Degenerative changes were present in 66.6% of OAs. The results of this evidence‐based anatomical review support a genetic basis for OA rather than the mechanical trauma‐induction hypothesis.